Effect of Temperature-Force Factors and Concentrator Shape on Impact Fracture Mechanisms of 17Mn1Si Steel - S. V. Panin; P. O. Maruschak; I. V. Vlasov; D. D. Moiseenko; F. Berto; A. Vinogradov (Advances in Materials Science and Engineering)
The influence of the notch shape on the impact fracture of 17Mn1Si steel is investigated at different temperatures with the focus placed on the low-temperature behavior. An approach towards fracture characterization has been suggested based on the description of elastic-plastic deformation of impact loaded specimens on the stage of crack initiation and growth at ambient and lower temperatures. The analysis of the impact loading diagrams and fracture energy values for the pipe steel 17Mn1Si revealed the fracture mechanisms depending on the notch shape. It was found that the testing temperature reduction played a decisive role in plastic strain localization followed by dynamic fracture of the specimens with differently shaped notches. A classification of fracture macro- and microscopic mechanisms for differently notched specimens tested at different temperatures was proposed which enabled a self-consistent interpretation of impact test results.